Investigation of groundwater development in four areas of Ido local government resistivity method (2010)
"This study focuses on the use of geo-electrical sounding for groundwater prospecting in four areas namely Ido Motor Park, (N 07° 18' 40.3"", E 003° 50' 29.2"") Elere- Apata '(N 07° 18' 40.3"", E 003° 50' 29.2"") Bakatari (N07° 18'40.3"", E 003'50'29.2'') and Apete Market (N07° 18' 40.3"", E 003°50' 29.2"") in Ido local government area Southwestern Nigeria. Two (2) Vertical electrical soundings (VES) were carried out using Schlumberger configuration at each of the selected area making a total of eight VES in the four selected areas of the local government. The field resistivity data acquired were plotted on bilogarithm paper and preliminary interpretation was carried out using partial curve matching involving two - layer master curves and the appropriate auxiliary chart. The layered models obtained were subjected to computer iteration using WIN RESIST Version 1 .O. The results of the sounding reveal a system of three to four geo-.electric layers of resistivity ranging from 126.7Ὠm to141 8.8Ὠm Deeply weathered material is quite evident within the premises: Groundwater development in the study area would be feasible if the deeply weathered / fractured basement is fully penetrated. "